Efeitos da dieta suplementada com disseleneto de difenila sobre a toxicidade induzida por mercúrio em camundongos e peixes - Fiuza, Tiago da Luz (2019)
With the increase of industrial and agricultural activities, several contaminants are released into the environment. Contaminants such as mercury (Hg) can come from the use of agricultural practices, burning of fossil fuels and mining activities, and this is highlighted in Brazil. Once released into the environment Hg reaches the aquatic and terrestrial environments and consequently the organisms that live there. In order to minimize possible toxic effects on non-target organisms, the use of food additives with antioxidant properties may be a good alternative. Diphenyl diselenide (PhSe)2, is an organic compound of selenium with antioxidant properties, and has beneficial effects in the treatment of animals exposed to heavy metals. Thus, the objective of this work was to evaluate the effect of a diet supplemented with (PhSe)2 on mercury chloride (HgCl2) -induced toxicity. Adult jundias (40-50g) and albino Swiss mice (25-30g) were used which were treated for 30 consecutive days with feed supplemented with (PhSe)2 or control ration. After 25 days of treatment the animals received a daily dose of HgCl2 solution (1.7mg / kg, fish, 5.0mg / kg mice) for 5 days. The animals were euthanized 24 hours after the last administration of HgCl2 and blood, renal and hepatic tissues were collected for analysis of the activity of the enzyme δ-aminolevulinate dehydratase (δ-ALA-D). Hepatic toxicity parameters (aspartate aminotransferase AST and alanine aminotransferase ALT), renal (urea and creatinine) and oxidative parameters (TBARS, total and non-protein thiols and reactive oxygen species) were evaluated. Fish exposed to Hg showed inhibition of δ-ALA-D activity of kidney and blood, increase in serum creatinine levels and decrease of TBARS, total thiols and non-protein thiols of kidney. Hg accumulated in the liver and kidneys of the fish causing alteration in zinc (Zn) homeostasis in the liver and blood tissues. Feeding with (PhSe)2 partially prevented the inhibition of renal δ-ALA-D, elevated serum creatinine levels, decreased levels of TBARS and non-protein thiols, as well as alteration in blood Zn homeostasis. Mice exposed to Hg showed inhibition of blood δ-ALA-D and serum ALT activity, increased urea and creatinine levels, decreased levels of TBARS and total renal thiols and increased levels of non-protein thiols in the kidney. Hg accumulated in the liver and kidney of mice and caused alteration in kidney Zn homeostasis. O (PhSe)2 completely prevented inhibition of blood δ-ALA-D, increase in urea and creatinine, and decrease of total kidney thiols and partially inhibition of serum ALT. Considering the results, it is believed that (PhSe)2 may prove to be a potential additive against Hg poisoning for both fish and mammals.